Stock-Flow Adjustments, Government's Integrated Balance Sheet and Fiscal Transparency - Seiferling, Mike (IMF Working Papers; Working Paper ;, 2013)
This paper re-examines the stock-flow discrepancies of government debt and deficits and correlation with fiscal transparency. Applying the fully integrated relationship between financial stocks and flows allows for a more refined analysis of the deterministic components that make up the 'stock-flow' residual. Using partial measures of these stock-flow residuals, several empirical studies have found them to be significantly correlated with fiscaltransparency, inflation, fiscal rules, and banking crisis. Using fully integrated public finance data from the IMF Government Finance Statistics Yearbook for a sample of 22 countries, the findings in this paper suggest that stock-flow residuals have a significantly smaller magnitude than previously assumed and are, in fact, not correlated with fiscal transparency. A stronger determinant of fiscal transparency scores appears to be the actual reporting of fiscal data covering general government, especially a full financial balance sheet.